STRATEGI PENGEMBANGAN WINE TOURISM DI HATTEN WINE BALI - Ni Wayan Astri Utami; Moch Nur Efendi; I Wayan Eka Mahendra (Universitas Triatma Mulya, 2023)
This research aims to develop a strategy for developing educational tourism in Hatten Wine. This research uses a qualitative descriptive approach with interview, observation, documentation and discussion group forum (FGD) methods. The results of this research show several attractions and facilities such as vineyards, wineries and wine cellars. The main facilities that other producers do not have are the oak barrel room and sparkling room, which are the only ones in Indonesia. and there is a Hatten education center as an official institution for certified wine training. For tourist activities that can be done in Hatten, such as seeing the wine making process, how to grow grapes as a basic ingredient for making wine, wine knowledge, wine serving and wine pairing. Various efforts have been made to increase tourist visits, such as creating wine class programs, international certification and wine events. However, development strategies are still needed to increase visits, such as: Creating a wine tourism program and collaborating with travel agents and tour operators in promoting educational tourism programs and also completing tourist facilities such as the new winery that Hatten plans to build which is more spacious and complete.